THE AUDIT QUALITY BATTLEGROUND: AI, PROFESSIONAL SKEPTICISM, EXPECTATION GAPS, AND AUDIT PROCESS EFFECTIVENESS FIGHTING FOR DOMINANCE IN SURABAYA’S PUBLIC ACCOUNTING FIRMS - Arti Mirza Aulia; Tri Ratnawati (Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines the simultaneous influence of professional skepticism, audit artificial intelligence (AI) utilization, and the expectation gap on audit quality, with audit process effectiveness serving as the mediating variable. Using a quantitative approach, data were collected through structured questionnaires distributed to auditors working in Public Accounting Firms (KAPs) across Surabaya. The results indicate that professional skepticism and the expectation gap have significant positive effects on both audit process effectiveness and audit quality, while AI utilization shows no significant effect on either variable. The findings highlight that human and perceptual factors remain dominant determinants of audit outcomes, and audit process effectiveness plays a crucial mediating role that translates auditor behavior and stakeholder perceptions into improved audit quality. The study concludes that technological adoption alone is insufficient without adequate auditor competence and organizational readiness. Theoretically, this research reinforces behavioural auditing and stakeholder theory, while practically, it emphasizes the need to strengthen professional skepticism, manage expectation alignment, and gradually integrate AI-based audit tools supported by proper training and digital capability.